Dietary micronutrients in the wake of COVID-19: an appraisal of evidence with a focus on high-risk groups and preventative healthcare. Issue 1 (18th June 2020) - McAuliffe, Shane; Ray, Sumantra; Fallon, Emily; Bradfield, James; Eden, Timothy; Kohlmeier, Martin
Abstract : Existing micronutrient deficiencies, even if only a single micronutrient, can impair immune function and increase susceptibility to infectious disease. Certain population groups are more likely to have micronutrient deficiencies, while certain disease pathologies and treatment practices also exacerbate risk, meaning these groups tend to suffer increased morbidity and mortality from infectious diseases. Optimisation of overall nutritional status, including micronutrients, can be effective in reducing incidence of infectious disease. Micronutrient deficiencies are rarely recognised but are prevalent in the UK, as well as much more widely, particularly in high-risk groups susceptible to COVID-19. Practitioners should be aware of this fact and should make it a consideration for the screening process in COVID-19, or when screening may be difficult or impractical, to ensure blanket treatment as per the best practice guidelines. Correction of established micronutrient deficiencies, or in some cases assumed suboptimal status, has the potential to help support immune function and mitigate risk of infection. The effects of and immune response to COVID-19 share common characteristics with more well-characterised severe acute respiratory infections. Correction of micronutrient deficiencies has proven effective in several infectious diseases and has been shown to promote favourable clinical outcomes. Micronutrients appear to play key roles in mediating the inflammatory response and such effects may be enhanced through correction of deficiencies. Many of those at highest risk during the COVID-19 pandemic are also populations at highest risk of micronutrient deficiencies and poorer overall nutrition. Correction of micronutrient deficiencies in established COVID-19 infection may contribute to supporting immune response to infection in those at highest risk. There is a need for further research to establish optimal public health practice and clinical intervention regimens.